Investigation of thixoforming process to enhance mechanical properties for automotive components production - Ahmad, Asnul Hadi; Ishak, M.; Rashidi, Maarof Mohd; Zakri, Ghazali (2019)
This research presents the works on the behaviour of aluminium 6061 which processed via thixoforming route for automotive components. Thixoforming is a forming process which exploits metal rheological behaviour during solidus and liquidus range temperature. Many research works in thixoforming are currently focusing on the raw material used to produce superior mechanical properties and excellent formability components, especially in automotive industries. Furthermore, the thixoforming process also produced less casting defect components such as macrosegration, shrinkage and porosity. The direct thermal method is one of the methods to create a globular microstructure feedstock billet, which gives the material a thixotropic behaviour during semisolid metal processing. In this experimental work, a molten aluminium 6061 was poured into a cylindrical copper mould before quenched in water at room temperature. The effect of pouring temperature of 660°C and 700°C and holding time of 20s and 60s were observed from the microstructure formation. The result shows that the combination of a pouring temperature of 660°C with a 20s holding time produces a finer near globular microstructure. These fine near globular microstructures gives a thixotropic behaviour improvement in better fluidity for a better flow during shaping. The design and manufacturing dies and molds are very important and vital tools to make sure that semi-solid metal processing process can produce high-quality product. The part was designed by using computer-aided design and fabricated by using a CNC machine. The design and product specification are very important aspects in order to make sure that die manufacturing followed the predetermined criteria. The works also aim to manufacture a die for automotive exhaust valve which is one of the components in a car engine. This research objective also to investigate the parameters that involve in thixoforming operations using hydraulic press machine such as pouring temperature, injection pressure, packing time and die temperature.